2015
DOI: 10.1051/0004-6361/201526705
|View full text |Cite
|
Sign up to set email alerts
|

New observations and models of circumstellar CO line emission of AGB stars in theHerschelSUCCESS programme

Abstract: Context. Asymptotic giant branch (AGB) stars are in one of the latest evolutionary stages of low to intermediate-mass stars. Their vigorous mass loss has a significant effect on the stellar evolution, and is a significant source of heavy elements and dust grains for the interstellar medium. The mass-loss rate can be well traced by carbon monoxide (CO) line emission. Aims. We present new Herschel/HIFI and IRAM 30 m telescope CO line data for a sample of 53 galactic AGB stars. The lines cover a fairly large rang… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
117
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 80 publications
(135 citation statements)
references
References 60 publications
(64 reference statements)
16
117
1
1
Order By: Relevance
“…This generally leads to overly resolved model line-profiles for the lower transitions, as evidenced by the double-peaked model line-profiles (specifically discussed for R Dor by Olofsson et al 2002). This is a common problem in CO radiative-transfer models (e.g., Justtanont et al 2005;Maercker et al 2008;Danilovich et al 2015). We attempted to fit the low-J line profiles by reducing the CO envelope size.…”
Section: Co Modelsmentioning
confidence: 99%
“…This generally leads to overly resolved model line-profiles for the lower transitions, as evidenced by the double-peaked model line-profiles (specifically discussed for R Dor by Olofsson et al 2002). This is a common problem in CO radiative-transfer models (e.g., Justtanont et al 2005;Maercker et al 2008;Danilovich et al 2015). We attempted to fit the low-J line profiles by reducing the CO envelope size.…”
Section: Co Modelsmentioning
confidence: 99%
“…Herschel/HIFI observations: The 12 CO J=5-4, 9-8, and 14-13 observations were part of the Herschel SUCCESS program (Teyssier et al 2011;Danilovich et al 2015) and observed with the onboard instrument HIFI (de Graauw et al 2010). The signal-to-noise ratio of the 12 CO J=14-13 line was about 2 to 3 and because of this high uncertainty we decided to omit this line from our analysis.…”
Section: Previously Published Co Radio Line Observationsmentioning
confidence: 99%
“…1, respectively. The technical setup, data reduction, and line profiles were published in Danilovich et al (2015). The line profiles were plotted in main beam temperature scale with a noise rms of 15 mK at a channel resolution of 3 km s −1 .…”
Section: Previously Published Co Radio Line Observationsmentioning
confidence: 99%
“…The sample was chosen to cover a range of mass-loss rates across all three chemical types, and was largely drawn from stars covered by the SUC-CESS programme (Danilovich et al 2015), for which high quality CO observations and mass-loss rates derived from CO modelling were already available. Of this sample all but two sources were observed for at least one of three possible H 2 S transitions and H 2 S was detected in three of these.…”
Section: Sample and Observationsmentioning
confidence: 99%